Pengaruh Penggunakan New Media Tiktok Terhadap Pembentukan Konsep Diri Generasi Muda Indonesia 2022 - Idza Carolin; Grace Deborah Victoria; Sarah Dina; Muhamad Nastain (CV. ITTC INDONESIA, 2023)
Tiktok is one of the new media that is widely used by the younger generation, this TikTok is an application that anyone can download that contains short interesting video content, many people always think that TikTok is only for entertainment, even though TikTok is a platform that is currently very influential. so that it can have a big impact on its users. This study aims to look further at the use of new media TikTok, as well as analyze the impact of using TikTok on the younger generation. In this study, we will discuss the impact of using TikTok on the younger generation in using the TikTok application and the impact on them. How do the younger generation use TikTok? What impact will it have on those who use the TikTok app? These questions will be the focus of this research. The sample we use is general with respondents totaling 312 Indonesian young people. The analytical method that will be used in this research study is a quantitative research method in which this research will be based on the data that has been collected to be able to understand the phenomena that occur and this research uses the theory of interactionism and the theory of media dependence. As for the results obtained, there is an influence between the use of the new media tiktok and the formation of self-concept in Indonesia.